STUDI PERANAN SEKTOR INFORMAL DALAM MENINGKATKAN PENDAPATAN KELUARGA BERPENGHASILAN RENDAH DI KECAMATAN TUMINTING KOTA MANADO - Kiyai, Burhanuddin; Ruru, Joorie Marhaen (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: This study is moved from the initial observation that informal scores, especially the motherhousewifebaker government received less attention in terms pemberdayaanya. Thus, this study aims todescribe the role of the informal sector in increasing people's income, khsusunya low-income families inthe District Tuminting. This research uses descriptive-analytic method. Purposive sample drawn as manyas 45 respondents mother-housewife wet cake maker and pastries. Data were collected through surveysand direct observation techniques using instruments Questionnaire. Once the data is collected, and thenanalyzed using analytical techniques frequency table and cross table.Having analyzed the results obtained as follows: (1) The business of the informal sector, especially bakinghas an important role in increasing the income of low-income people, especially for mothers ofhouseholds to help meet the needs of their families. (1) Most businesses informal sector, especiallymothers cake makers (wet and dry) to get working capital from a third party (the release of money / loanshark) or cooperative with relatively high interest, because they do not understand the procedures andterms of the loan capital Work through the bank. This reality is a consequence of the lack of socializationof business credit (KUR) channeled government.Thus, the conclusion that can be drawn from these results is that the factors formal education, skills andworking capital is a determinant (determinant) increase in operating income in the informal sector,especially the business of making pastries and cakes by the mother-housewife from low-income families inthe District Tuminting.Suggestions or recommendations can be given, anatar others: governments need to streamline thedissemination of KUR and provide guidance and empowerment to businesses cake maker, through ease ofaccess memdapatkan scholarship vocational school for the children of the target group, the ease of accessto business loans KUR and provide training job skills, especially in the field yeknik cake-making andmanagement of usaaha.Keywords: Informal sector, Cake Makers, family income